2020
DOI: 10.3390/app10196742
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Studies of the ŁK Type Shaped Charge

Abstract: In this paper, the authors presented an analysis of the strengthening of the cumulative jet by the appropriate formation of the detonation wave front acting under the influence of high pressure on the liner. The analysis of the Polish ŁK cumulative charge was carried out using numerical methods in the ABAQUS program. Simulation studies were carried out on axial and peripheral initiations of the explosive cumulative liner. For this purpose, two types of cumulative charges were made with the same design paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Although, multiple studies on the effectiveness of various HEAT warheads with different numbers of SCs [21,22], liner shapes [23][24][25], liner materials [26][27][28], and types of explosives used [29] were presented in the literature, paradoxically there is a lack of accurate and reliable research related to the performance of the most common PG-7VM warhead. In the available studies related to PG-7VM efficiency, the geometry of the warhead is often modeled in an inappropriate or too simplified way and the results are usually limited to the value DoP in RHA steel.…”
Section: Introductionmentioning
confidence: 99%
“…Although, multiple studies on the effectiveness of various HEAT warheads with different numbers of SCs [21,22], liner shapes [23][24][25], liner materials [26][27][28], and types of explosives used [29] were presented in the literature, paradoxically there is a lack of accurate and reliable research related to the performance of the most common PG-7VM warhead. In the available studies related to PG-7VM efficiency, the geometry of the warhead is often modeled in an inappropriate or too simplified way and the results are usually limited to the value DoP in RHA steel.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and material nature of Cu foil, which affects the energy deposition, plasma output ability and flyer velocity, is the most researched topic on exploding foil detonators [1][2][3], which are considered as the key materials for electronic safe and arm systems for rocket motor ignition, fuzing, ammunition, and flight termination applications [4][5][6][7][8][9][10][11][12]. The velocity and shape of the flyer are two key factors that affect the energy-output effect of exploding foil initiators.…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the direction of the electromagnetic field, the penetration ability of the SCJ can be improved or reduced. Pyka et al [ 12 ], through theoretical research and numerical tests on two types of the Polish ŁK cumulative charge, showed that the jet still retains its ability to penetrate after penetrating the shield. It follows that this ŁK charge can effectively pierce shields of this type with a thickness of more than three calibers.…”
Section: Introductionmentioning
confidence: 99%